Pros and Cons Toward Multiculturalism and Education Multikulcuralism - stainu, ghazali; Lestari, Prawidya (STAINU Purworejo, 2018)
This study aims to analyze multiculturalism and multicultural education in general, then will be presented in broad outline, regarding the views of the pros and cons who emerged as a reaction response to the concept of multiculturalism and the concept of multicultural education. This type of research is literature (Library Research) is research by collecting data that have relevance to the issues discussed, whether it comes from books or other written sources (papers, articles, journals or research reports). Data collection techniques conducted in this research is the determination of the issues discussed, digging information according to problems and data analysis. The result of this research can be concluded that (1) Multiculturalism is as a understanding and multicultural education is dimension of praxis of multiculturalism, (2) Implementation of multicultural education in Indonesia has not been done as expected because this discourse is relatively new and is still a matter of debate between leaders and experts. So this concept is new in the on going process and will continue to be tested in the field, (3) Differences in the opinion of multicultural education is due to various matters, especially related to the issue of beliefs and attitudes that are exclusive of the adherents, causing conflict.Keynote: